Kejujuran Mahasiswa Pendidikan Agama Islam dalam Konteks Akademik - Kamila Nur Aini; Risda Retno Aji Puspa Utami; Nindi Ayu Apriliana (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Students of Islamic Education Study Program at UIN Raden Mas Said Surakarta have a goal to produce professional islamic education educators, with Islamic character, high quality, and technology-based. However, most students attitudes are still not in accordance with the meaning of islamic education itself. Indicators of honesty are still not reflected in them, especially in carrying out academic activities. This study aims to determine the honesty of islamic education students in an academic context. The method used in this research is qualitative research with data collection techniques through semi-structured interviews involving three informants. The data collection technique in study was purposive sampling with criteria: sixth semester islamic education students, staying in islamic boarding school, and had never been the subject of previous research. As a result, students have not fully implemented academic honesty and still have a tendency to cheat, plagiarize, lie and do unusual things in completing academic tasks.